Origin of an Uncommon Multiple‐Stroke Positive Cloud‐to‐Ground Lightning Flash With Different Terminations. Issue 15 (6th August 2020) - Yuan, Shanfeng; Qie, Xiushu; Jiang, Rubin; Wang, Dongfang; Sun, Zhuling; Srivastava, Abhay; Williams, Earle
Abstract: An uncommon three‐stroke positive cloud‐to‐ground (+CG) lightning flash was observed by synchronous multifrequency radiation sensors, and the three‐dimensional development of the channel was carefully mapped. Results show that three positive strokes grounded at different points approximately 4–8 km apart and time intervals between neighboring +CG strokes were 85 and 222 ms, respectively. This +CG flash was preceded by an intracloud (IC) discharge. The locations of the termination points on the ground were just below the preestablished horizontal IC discharge channels, and the three strokes were linked with each other through sharing horizontal negative leader channels inside the cloud. There were stepping pulses less than 0.4 ms before the first and second return strokes (RSs), and their location results were distributed nearby the following RS, indicating that the pulses might be associated with the attachment process. The first and second positive strokes occurred when the horizontal in‐cloud negative channel stopped extending, while the third positive stroke occurred below the opposite end of an advancing negative leader in the cloud. The above results suggest that the downward positive leader preceding the strokes possibly developed either from different decayed leader channels or from the opposite end of an advancing leader channel. A high‐speed camera captured a downward positive attempted leader from another +CG flash, revealing how a downward positive leader incepted from a horizontal negative lightning channel. Plain Language Summary: Positive cloud‐to‐ground (+CG) lightning flashes transfer the positive charge from a cloud to the ground and usually have only one return stroke (RS). The development of multistroke positive lightning remains poorly understood. Here we report how a three‐stroke +CG flash occurred based on the 3‐D lightning radiation mapping method, and the results revealed that the +CG flash was preceded by an intracloud (IC) discharge. Three +CG RSs terminated on totally different points, but they were all right below the preestablished horizontal lightning channels inside the cloud, which confirmed that they belong to one lightning flash rather than independent three +CG strokes. In the tens of milliseconds before +RS1 and +RS2, there was no obvious in‐cloud lightning activity (the leaders remained quiet), while developing in‐cloud leader was found preceding the occurrence of +RS3. A high‐speed video of another +CG flash revealed how the downward positive leader could initiate from a horizontal negative leader channel. Key Points: An uncommon three‐stroke positive cloud‐to‐ground lightning flash was detected with synchronized multifrequency radiation sensors Three positive strokes terminated at different ground points, but they were associated with channels of an same IC discharge A downward positive leader possibly developed from either a decayed negative channel or the opposite end of an advancing negative leader